2018
DOI: 10.1101/456459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The essential role of feedback processing for figure-ground perception in mice

Abstract: AbstractThe segregation of figures from the background is an important step in visual perception. In primary visual cortex, figures evoke stronger activity than backgrounds during a delayed phase of the neuronal responses, but it is unknown how this figure-ground modulation (FGM) arises and whether it is necessary for perception. Here we show, using optogenetic silencing in mice, that the delayed V1 response phase is necessary for figure-ground segregation. Neurons in higher vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
(94 reference statements)
1
3
0
Order By: Relevance
“…Our finding that figure-ground signals exist in mouse visual cortex ( Figures 3e, f , 4 , and 5d, i ), but are strongly dependent on texture ( Figures 4 and 5a, b, e, i–k ), is consistent with previous studies ( Schnabel et al, 2018a ; Kirchberger et al, 2020 ; Schnabel et al, 2018b ; Keller et al, 2020b ). Optogenetic perturbation studies have further demonstrated that these signals are behaviorally relevant for figure detection ( Kirchberger et al, 2020 ) and require feedback ( Kirchberger et al, 2020 ; Keller et al, 2020a ). Thus overall, it seems clear that mouse visual cortex shows orientation-dependent surround modulation ( Self et al, 2014 ; Keller et al, 2020a ) which can support texture-based figure-ground segmentation behavior.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that figure-ground signals exist in mouse visual cortex ( Figures 3e, f , 4 , and 5d, i ), but are strongly dependent on texture ( Figures 4 and 5a, b, e, i–k ), is consistent with previous studies ( Schnabel et al, 2018a ; Kirchberger et al, 2020 ; Schnabel et al, 2018b ; Keller et al, 2020b ). Optogenetic perturbation studies have further demonstrated that these signals are behaviorally relevant for figure detection ( Kirchberger et al, 2020 ) and require feedback ( Kirchberger et al, 2020 ; Keller et al, 2020a ). Thus overall, it seems clear that mouse visual cortex shows orientation-dependent surround modulation ( Self et al, 2014 ; Keller et al, 2020a ) which can support texture-based figure-ground segmentation behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Behaviorally, mice are capable of texture-based segmentation, in which figure and background are defined by grating patterns with different orientation and/or phase ( Kirchberger et al, 2020 ; Schnabel et al, 2018a ). Consistent with this behavioral capability, cells in mouse V1 show iso-orientation surround suppression ( Self et al, 2014 ; Keller et al, 2020a ) and have been reported to be modulated by figure versus ground ( Schnabel et al, 2018a ; Kirchberger et al, 2020 ; Keller et al, 2020b ). However, all these studies have used texture-based cues, which are fundamentally ambiguous for solving segmentation ( Figure 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…The visual system of the primate is somewhat different from that of the rodent, however. The primate has forward-looking eyes, and the movements of the eyes are conjugate, allowing for stereovison, and disjunctive when changing depth planes (Carpenter 1988, Schiller & Tehovnik 2015, Zhou & King 1998. In the rodent, however, the laterally placed eyes offer extended coverage of the visual field, which is important for predator avoidance (De Franceschi et al 2016, Ellard & Chapman 1991, Meister & Cox 2013, Wallace et al 2013, Yilmaz & Meister 2013.…”
Section: From Primate To Rodent Brainmentioning
confidence: 99%
“…Optogenetic perturbation studies have further demonstrated that these signals are behaviorally relevant for 10 figure detection [29] and require feedback [29,31]. Thus overall, it seems clear that mouse visual cortex shows orientation-dependent surround modulation [15,16] which can support texture-based figure-ground segmentation behavior.…”
Section: Discussionmentioning
confidence: 95%
“…Behaviorally, mice are capable of texture-based segmentation, in which figure and background are defined by grating patterns and have different orientation or phase [29,30]. Consistent with this behavioral capability, cells in mouse V1 show iso-orientation surround suppression [15,16] and have been reported to be modulated by figure versus ground [29][30][31]. However, all of these studies have used texture-based cues, which are fundamentally ambiguous for solving segmentation (Fig.…”
Section: How Could the Brain Solve Visual Segmentation?mentioning
confidence: 87%